“Decorative” and “Religious” Statues: Boundaries between Artistic and Religious Components in Graeco-Roman Paganism and Judaism in the Beginning of the Common Era - Panteleev, Aleksey D. (Actual Problems of Theory and History of Art, 2019)
In the Hellenistic-Roman period the Jews faced the urgent problem of determining the permissible and impermissible in contact with other cultures of the ancient world. One of its aspects was the question of statues of pagan deities, kings and emperors. They were not only in temples, but also in public spaces — streets, markets, courthouses, etc. The Jews were faced with these sculptures both in the Diaspora and in Palestine. The prescriptions contained in the Pentateuch were, in practice, hard to follow in their totality. The Second Commandment forbids the Jews from creating idols (Ex 20, 4, Deut. 5, 8), and it was perfectly possible to observe, but other instructions were obviously impossible (Ex 23, 24; Ex 34, 13). Philo of Alexandria and Josephus Flavius informed us about the first problems connected with sacred images, and later the discussion about them would become the main theme of the third chapter of the treatise “Avodah Zarah”, which is part of the Babylonian Talmud.In our paper we consider three issues discussed in “Avodah Zarah”: the definition of a cult statue; the definition of a place that served the worship of gods; and the “desacralization” of the cult statues. Rabbis of the 2nd–4th centuries CE created a list of formal attributes that made it possible to distinguish a sacred sculpture from a decorative statue (the presence of a scepter, a bird, a ball, a snake, etc.), but in addition, the attitude of the Gentiles themselves to these statues played an important role. The fundamental role here is played by Gamaliel’s words about the permissibility of using the thermae, if it’s decorated with the statue of Aphrodite. In addition, Y. Furstenberg directly points to the parallels between the destructive actions produced by the Romans in the rituals of damnatio memoriae, the curse of the memory of the “bad” emperor, and the principles by which the rabbis are guided in establishing the permissible and unauthorized.
Keywords: Roman Empire; Palestine; statues; Avodah Zarah; ancient religion; early Judaism; Imperial cult